Маленький принц - Сент-Экзюпери Антуан де (АВИГ, 1992)
Экземпляры: Селтинская районная библиотека (к/х) (20210903) / Инвентарный номер: 170410 / Цена: / Авт.знак: С 31 / ГРНТИ: 17.82.30 / ББК: 84(4Фра)